1991
DOI: 10.21273/jashs.116.4.651
|View full text |Cite
|
Sign up to set email alerts
|

Soil Disinfection and Monoammonium Phosphate Fertilization Increase Precocity of Apples on Replant Problem Soils

Abstract: In an apple (Malus domestica Borkh.) orchard with a severe replant problem, tree size was increased by the 2nd year and number of fruit by the 3rd year by treating the planting hole soil with formalin or mancozeb plus monoammonium phosphate (MAP) fertilizer. Growth increases were evident each year for 4 years only for the MAP + formalin treatment. In a second orchard, with a less severe replant problem, planting-hole treatment with formalin or dazomet + MAP increased tree siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…surface applications of monoammonium phosphate (MAP) fertilizer (Raese, 1998). Application of 150 g of MAP fertilizer within the planting hole, in association with some form of soil disinfection, has improved establishment and initial growth of apple in replant problem orchards (Neilsen and Yorston, 1991). As a consequence of stimulation of second-year flowering by first-year P applications (Neilsen et al, 1990) and the effectiveness of first-year P fertigation , P fertigation of newly planted apple trees in the first year is a general commercial recommendation regardless of soil P and replant status (BC Ministry of Agriculture and Lands, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…surface applications of monoammonium phosphate (MAP) fertilizer (Raese, 1998). Application of 150 g of MAP fertilizer within the planting hole, in association with some form of soil disinfection, has improved establishment and initial growth of apple in replant problem orchards (Neilsen and Yorston, 1991). As a consequence of stimulation of second-year flowering by first-year P applications (Neilsen et al, 1990) and the effectiveness of first-year P fertigation , P fertigation of newly planted apple trees in the first year is a general commercial recommendation regardless of soil P and replant status (BC Ministry of Agriculture and Lands, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, several conditions have been identified when apples respond to P fertilization. These include times when apple root length is limited, as when trees are newly planted (Taylor and Goubran, 1975) and when replant disorders further inhibit root growth (Neilsen and Yorston, 1991), or when low soil P levels limit P availability to roots (Cripps, 1987;Raese, 1998). Responses to P application have included increased vigor and accelerated flowering of newly planted trees (Neilsen et al, 1990;Taylor and Goubran, 1975) and increased cropping and increased P concentrations in leaf and fruit tissue of mature trees (Cripps, 1987;Raese, 1998).…”
mentioning
confidence: 99%
“…The differential uptake of P among treatments reflected the higher P inputs associated with the CDS amendment (Table 1) and the highest available soil P values for CDS-amended soils at the end of the experiment (Table 5). Application of monoammonium phosphate in the planting hole has been shown to stimulate apple tree growth in old orchard soils (Neilsen and Yorston, 1991) and was the rationale for fertigation of ammonium polyphosphate to all treatments in this experiment in Year 1. Highest leaf P concentrations were measured in the first year, but midsummer leaf P concentrations, regardless of treatment, generally exceeded 1.5 g P/kg values normally considered adequate for apples (Shear and Faust, 1980).…”
Section: Soil and Plant Nutrientsmentioning
confidence: 97%
“…Injection of nitrogen fertilizers through the drip irrigation system (fertigation) is becoming increasingly popular in major fruit growing areas of the would [Haynes, 1985]. High rates of monoammonium phosphate (MAP) incorporated directly into planting holes have improved vigour [Neilsen and Yorston, 1991] and precocity of apply trees [Neilsen et al, 1990]. Recently, Neilsen et al [1993] showed that apple trees fertigated with calcium nitrate had increased early vigour compared to trees fertigated with urea or ammonium nitrate.…”
Section: Introductionmentioning
confidence: 99%